(untitled) (Journal of Medical & Health Sciences Review, 2025)
The six-minute walk test (6MWT) is a simple and low-tech assessment that has proven to be reproducible and well-tolerated since its introduction. However, the influence of non-anthropometric factors on functional capacity in healthy young adults remains unclear, as most do not exhibit age-related changes in the locomotor system or comorbidities. The aim of the study was to enhance our understanding of how these factors (e.g. physical activity level, dyspnoea severity, and pulmonary function) influence functional capacity (exercise performance), with implications for preventing clinical abnormalities and promoting overall health and well-being. This cross-sectional study involved 330 healthy young adults who completed the 6MWT to measure walking distance and dyspnoea using the Borg scale. Pulmonary function was assessed with spirometry, and physical activity level was categorized using the IPAQ Questionnaire, classifying participants irregularly active and active. The 6MWD was positively correlated with pulmonary function parameters (P ≤ 0.002 for all). There was marginally significant correlation between 6MWD and the change in Borg scale scores before and after the test. Additionally, there was a trend toward significant differences in 6MWD across IPAQ categories. Forced vital capacity was the only pulmonary function parameter significantly different between IPAQ categories (P = 0.02).This study demonstrates that in healthy young adults, better pulmonary function is associated with a longer 6-minute walk distance (6MWD). Physical activity levels, as categorized by the IPAQ, seem to influence pulmonary function, particularly forced vital capacity (FVC).However, there is a weak relationship between IPAQ categories, the degree of dyspnea, and the 6MWD in these individuals.